2012
DOI: 10.2319/041912-326.1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment time, outcome, and anchorage loss comparisons of self-ligating and conventional brackets

Abstract: The treatment time and anchorage loss are not influenced by the type of bracket used. There are significant dental and skeletal changes among adolescent orthodontic patients regardless of the bracket used. There is significantly greater lingual inclination of mandibular incisors in the CB group than in the SLB group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 23 publications
0
31
1
6
Order By: Relevance
“…Recent reports showed that self-ligating brackets do not provide better anchorage control, especially with respect to less friction, which is believed to be obtained with self-ligating bracket systems. [4][5][6][7][8][9] The TPA has been widely used in orthodontics either with continuous or segmented arch mechanics to minimize anchorage loss and/or control rotation of the upper first molars. 1,3,[10][11][12][13][14][15][16][17][18][19][20] Although TPA has been shown not to improve anchorage control during space closure, many clinicians still believe that the TPA alone can control anchorage during space closure in orthodontic extraction cases.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports showed that self-ligating brackets do not provide better anchorage control, especially with respect to less friction, which is believed to be obtained with self-ligating bracket systems. [4][5][6][7][8][9] The TPA has been widely used in orthodontics either with continuous or segmented arch mechanics to minimize anchorage loss and/or control rotation of the upper first molars. 1,3,[10][11][12][13][14][15][16][17][18][19][20] Although TPA has been shown not to improve anchorage control during space closure, many clinicians still believe that the TPA alone can control anchorage during space closure in orthodontic extraction cases.…”
Section: Introductionmentioning
confidence: 99%
“…There is no difference in anchorage between the groups and therefore self-ligating brackets do not help to increase anchorage 26 .…”
Section: Managing Anchoragementioning
confidence: 99%
“…The articles showed no difference in the length of treatment between self and non self-ligating brackets 9,16,17,18,26 .…”
Section: Length Of Treatmentmentioning
confidence: 99%
See 2 more Smart Citations